A direção ético-política da prática do assistente social: uma análise no âmbito hospitalar público à luz do Projeto Profissional - Mamede, Eliane Leite (2009)
The purpose of this study is to analyze and understand the ethical-political direction taken by the professional practice of Social Worker in the public health, specifically in the field hospital of Joao Pessoa / PB. This theoretical production has become a critical-analytical study of quantitative and qualitative character, as a methodological procedure of analysis of the object. It is resulting from the investigation of the role of Social Service in 5 public hospitals, to large. 37 social workers were been interviewed, whose testimony about the daily practice of these professionals were faced with the proposal of hegemonic act of the category, expressed in the ethicalpolitical project of Social Service. In this process, tried to seize the objective and subjective conditions of the interviewed. From the data found that within public hospital is found dead of a different objective, fruit of the consolidation of neo-liberal project of state in the country, challenges that arise as to the Social Worker forward in implementing its Project Ethical-Political and the Health Reform Project, which are: the gaps and lack of resources, poor quality of public services expressed in the slow and poor attendance, failure and traces of improvisation, creating ambiguities in the operation rules, the maintenance of neo-liberal hegemony that permeates the structures and existing social relations. Facing these challenges, social workers, usually, have activities that they respond, especially to institutional objectives, based on immediate and routines required by the contracting agency. Therefore, these professionals end up reinforcing the objectives of the institution and not the goals of the Project Ethical-Political Training. This project is known by the whole surface of the professionals interviewed, which compromises the interaction of multiple relationships that he inspires as well as the deal makes critical social needs and qualified professionals and contemporary. Finally, the research revealed that the ethical and policy direction in the prevailing practice of social workers is still that conformed to the cyclical trends and standards and institutional boundaries, reinforcing the reproduction of the existing order and its game of power. This reality has fracturing the historic achievements of the working class, but also compromises the quality and consistency of the theoretical and methodological heritage, built by the professional category, and thereby promoting the tearing of the ethical-political culture that includes the defense of social justice, the citizenship and democracy.